Nanoscale observations of magnesite growth in chloride- and sulfate-rich solutions - King, H.; Satoh, H.; Tsukamoto, K.; Putnis, Andrew (2013)
Magnesite growth in chloride and sulfate-rich solutions has been examined at 90 C in situ using phase-shift interferometry (PSI) and ex situ using atomic force microscopy (AFM) to evaluate the feasibility of cosequestering SO 2 and CO2 in Mg-rich rocks. Although sulfate may assist desolvation at the magnesite surface, evidence for enhanced growth was only found at specific surface sites. The overall growth rates fit with those observed for chloride experiments in similarly saturated solutions. Thus, the formation of Mg-SO4 ion pairs in solution, which lowers the supersaturation with respect to magnesite, will have the dominant effect during sequestration. Lowering the activity of Mg2+ ions in solution also inhibited the nucleation of other hydrated Mg-carbonate phases. As no evidence was found for sulfate incorporation into the growing magnesite, the presence of sulfate in solution will be detrimental to CO2 sequestration and is not expected to be cosequestered. The PSI data also emphasize the variability of reactivity over the surface and how this changes as a function of solution saturation and composition.